أساليب التنشئة الاجتماعية للطفل في الوسط الأسري- دراسة عينة من الأمهات - - كتفي, ياسمينة (Sciences de l'Homme et de la Société, 2016)
تناول البحث موضوع أساليب التنشئة الاجتماعية للطفل في الوسط الأسري حيث انطلق من حقيقة حاجة الطفل في مرحلة الطفولة لتنشئة اجتماعية داخل الوسط الأسري وأهمية التنشئة الأسرية، كما تعد الأسرة المهد الأول لتنشئة الفرد وأول خلية مسئولة عن تربيته وتنشئته، وتنمية بعض المهارات لديه، هذا ما كان دافعا للباحثتين لإثارة الموضوع وتسليط الضوء في هذه الورقة على أساليب تنشئة الطفل في الأسرة كوحدة اجتماعية هامة إلا أن دورها التربوي أكثر أهمية.     Abstract: The subject of child socialization research in the family environment where research launched the need for the child is in the socialization of children within the family and the importance of family education, where the family is the first to cradle lift the person or the first cell is responsible for teaching and education, and contribute to the child's talents and develop some of the skills available to it, that's what provided the impetus to raise the issue and stresses in this document on child rearing practices in the family as an important social.